Shakespeare's sonnets - Muir, Kenneth (Routledge library editions. Shakespeare., 2005)
This edition first published in 1979. Discussing Shakespeare's sonnets in relation to sonnets by Italian, French and English poets, Kenneth Muir shows how they were influenced by Shakespeare's reading of Sidney, Erasmus and Ovid and discusses their art in terms of construction, sound patterns and imagery. He considers the relationship of the sonnets to Shakespeare's dramatic writing, while stressing the dramatic element in the sonnets themselves. Finally he surveys the changing attitudes to the sonnets during the last three centuries.